Coronary Artery Bypass Grafting in Patients with Reduced Left Ventricular Myocardial Contractility - Yurii V. Kashchenko; Anatoliy V. Rudenko (Український журнал серцево-судинної хірургії)
Coronary artery bypass grafting (CABG) is a crucial treatment for ischemic heart disease in patients with reduced left ventricular ejection fraction (LVEF). This approach improves survival and quality of life but carries a higher risk of complications. Off-pump CABG reduces the risk of strokes and bleeding, while on-pump CABG is beneficial for patients with complex anatomy. Planned use of cardiopulmonary bypass (CPB) stabilizes patients’ condition and reduces postoperative complications.